Sentence and the compound sentencein Julius Zeyer’s epic poetry and prose - SCHACHERL, Martin (Bohemistyka, 2021)
The aim of this paper is to explore the use of the sentence and the compound sentence in the literary works of the Czech poet Julius Zeyer (1841–1901). Specifically, we intend to make a quantitative identification of congruencies and parallels, typical of the syntactic structure of Zeyer’s epic poetry and prose, as evidenced by a detailed analysis of particular stylistic devices used in the selected representative texts. The aim of this paper is to corroborate, or possibly to exclude, the impact of the selected narrative means of expression on the stylistic and compositional variances of the text, which is facilitated by paying full attention to one aspect of Zeyer’s authorial style, namely, the quantitative variation of sentences and compound sentences.